The Kazakh Scientist of the 19th Century Chokan Valikhanov is a Founder Graphic Art of Kazakhstan (Global Journal of Human-Social Science, 2016)
The contents of article are devoted to studying of art heritage in the field of arts of the Kazakh scientist of Chokan Valikhanov - a bright phenomenon in the scientific sphere of Russia and Europe in of an eyelid In work on the basis of studying scientific literary links about art creativity and the brief excursion - analysis of drawings from a position of art criticism are proved a role and importance of studying preservation its heritage for enrichment of history of arts of Kazakhstan and in use of spiritual education of the younger generation
Keywords: scientist; art heritage; fine arts; portraits; importance studying; arts of Kazakhstan